2018
DOI: 10.1039/c8sc02041h
|View full text |Cite
|
Sign up to set email alerts
|

Iridium-catalyzed enantioselective direct vinylogous allylic alkylation of coumarins

Abstract: The first iridium-catalyzed enantioselective vinylogous allylic alkylation of coumarins is presented. Using easily accessible linear allylic carbonates as the allylic electrophile, this reaction installs unfunctionalized allyl groups at the γ-position of 4-methylcoumarins in an exclusively branched-selective manner generally in high yields with an excellent level of enantioselectivity (up to 99 : 1 er).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(9 citation statements)
references
References 70 publications
1
7
0
Order By: Relevance
“…On the basis of the observations presented above and previous reports, , a reasonable catalytic cycle is illustrated in Figure .…”
supporting
confidence: 58%
“…On the basis of the observations presented above and previous reports, , a reasonable catalytic cycle is illustrated in Figure .…”
supporting
confidence: 58%
“…In this context, the first iridium-catalyzed enantioselective vinylogous allylic alkylation of coumarins has been recently reported almost contemporarily and independently by the groups of Mukherjee and Yin in 2018 ( Scheme 197 ). In particular, using easily accessible linear allylic carbonates 773 , as allylic electrophiles (eq 1), Mukherjee and co-workers 510 found that [Ir(cod)Cl] 2 complexed with chiral ligand L27 effectively promoted the vinylogous allylic alkylation of 4-methylcoumarins 772 , in an exclusively branched-selective manner (>20:1 branched vs linear), affording the corresponding γ-adducts 774 in generally high yields (up to 98%) with an excellent level of enantioselectivity (up to 98%). Similarly, the catalytic asymmetric, vinylogous allylic alkylation of 4-methylcoumarins 772 and differently shaped, α,β-unsaturated lactones of type 776 was achieved by Yin et al 511 using allylic carbonates of type 775 and suitable ligands such as L27 or L28 to be complexed with [Ir(COD)Cl] 2 ( Scheme 197 , eqs 2 and 3).…”
Section: Vinylogous Esters and Lactonesmentioning
confidence: 99%
“…With our interest in Ir-catalyzed AAS reactions, we envisaged that the reaction of vinyl azide with an in situ generated electrophilic π-allyl–Ir complex could lead to an overall α-allylic alkylation of α-unsubstituted secondary acetamides (Scheme C).…”
mentioning
confidence: 99%